clean cuisine COOKBOOK : 130+ Anti-Inflammatory Recipes to Heal Your Gut, Treat Autoimmune Conditions, and Optimize Your Health - Larson, Ivy Ingram, 1976-; Larson, Andrew, 1973- (Las Vegas: Victory Belt Publishing, 2019)
"In their new book, The Clean Cuisine Cookbook, Ivy and Andy Larson deliver a revolutionary new approach to clean eating. Together they have created a cookbook that demystifies what it truly means to eat clean while offering a roadmap to lifelong health."
Clean Cuisine defined -- Ten Clean Cuisine dos and don'ts -- The diet Rx -- Understanding carbohydrates, fats, and proteins -- Stocking your Clean Cuisine kitchen -- Kitchen tools and equipment -- Clean Cuisine meals -- Start the day -- Snacks and such -- Soups and salads -- What's for dinner? -- Easy one-pot meals -- Meatless Mondays -- Simple sides -- Juices, elixirs, and cocktails -- No-milk shakes -- No-regrets sweet treats -- Clean Cuisine basics.
Includes index.
Includes bibliographical references and index.
Keywords: Autoimmune diseases -- Recipes. -- Diet therapy; Inflammation -- Recipes. -- Diet therapy; Cooking; Health; Cookbooks